The Navigasi dan Formasi Kawanan Robot Menggunakan Sistem Pemosisian Lokal dengan Sumberdaya Rendah: Sistem Pemosisian didalam ruangan - Helmy Widyantara; Mas Aly Afandi; Ristanti Akseptori; Ubaidilah Umar (Jurusan Teknik Elektro Universitas Andalas, 2022)
This paper discussed the method of navigation and robot formation in a swarm using the Local Positioning System (LPS) which was applied to the mobile robot's differential steering platform. Navigation and formation of robots in swarm robotics could run well because of the presence of robot position coordinates. In the outdoor application of coordinates, the position of the robot could be obtained easily using the Global Positioning System (GPS), but GPS had drawbacks in indoor applications. In indoor use, signals from satellites were difficult to obtain and inaccurate for use with relatively short distances. In coordinate research, positioning used LPS which was built using Bluetooth Low Energy (BLE). LPS with BLE was successfully built with simple resources and at a low price but had optimal performance. The LPS accuracy built with BLE and the regression algorithm had an error of 4.33% on the X-axis, and 2.67% on the Y-axis. The robot formation utilized a combination of proximity sensors and position coordinates obtained from LPS. The proximity sensor served to detect obstacles that hold the robot towards a predetermined target. The combination of navigation algorithms and swarm formation robotics was proven to be faster at finding targets compared to a single robot.